2011
DOI: 10.1088/0967-3334/32/11/s06
|View full text |Cite
|
Sign up to set email alerts
|

Time-variant partial directed coherence in analysis of the cardiovascular system. A methodological study

Abstract: Time-variant partial directed coherence (tvPDC) is used for the first time in a multivariate analysis of heart rate variability (HRV), respiratory movements (RMs) and (systolic) arterial blood pressure. It is shown that respiration-related HRV components which also occur at other frequencies besides the RM frequency (= respiratory sinus arrhythmia, RSA) can be identified. These additional components are known to be an effect of the 'half-the-mean-heart-rate-dilemma' ('cardiac aliasing' CA). These CA components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…They showed that the presence of instantaneous correlations may produce misleading profiles of PDC, whereas ePDC and iPDC provided a correct interpretation of extended and lagged causality, suggesting that ePDC and iPDC are more interpretable than PDC when applied to known cardiovascular and neuronal data. Milde et al [23] introduced a time-variant version of PDC (tvPDC) for short-term multivariate data analysis which is based on a time-variant MAR model in combination with a Kalman filter for model parameter estimation. The Fourier transform of the AR parameters is used to define tvPDC.…”
Section: (I) Linear Methodsmentioning
confidence: 99%
“…They showed that the presence of instantaneous correlations may produce misleading profiles of PDC, whereas ePDC and iPDC provided a correct interpretation of extended and lagged causality, suggesting that ePDC and iPDC are more interpretable than PDC when applied to known cardiovascular and neuronal data. Milde et al [23] introduced a time-variant version of PDC (tvPDC) for short-term multivariate data analysis which is based on a time-variant MAR model in combination with a Kalman filter for model parameter estimation. The Fourier transform of the AR parameters is used to define tvPDC.…”
Section: (I) Linear Methodsmentioning
confidence: 99%
“…Due to, that the original introduced PDC method cannot be applied to non-stationary signals a time-variant version is needed providing information about the partial correlative short-time interaction properties. In addition to, Milde et al [31], the normalized short time partial directed coherence (NSTPDC) was introduced for nonstationary signal to evaluate dynamic coupling changes and to detect the level and direction of couplings in multivariateand complex dynamic systems [32]. With the view to determining the coupling strength and direction between two time series, x and y, a coupling factor (CF) was proposed.…”
Section: Normalized Short Time Partial Directed Coherencementioning
confidence: 99%
“…In contrast, the instantaneous heart rate (IHR) representation is an approximation of the demodulation. The superiority of the LPFES (vs. IHR) for the investigation of rhythmic HRV components was shown by Milde et al [23]. The final HRV representation was obtained via multiplication of the LPFES with the sampling rate and with 60 beats per minute (bpm) and downsampled to 8 Hz.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%